Comparison of chemical properties of food products processed by conventional and ohmic heating - Pereira, Ricardo (2007)
The effect of ohmic and conventional heat processing of different food products on their chemical and physical parameters was studied. Depending on the food being analysed, parameters such as pH, total solids, ash, titratable acidity, ascorbic acid, total sugars, total fatty acids, total phenolic compounds, and anthocyanins content were determined before and after ohmic and conventional pasteurization techniques and the results were compared using one-way analysis of variance. In goat milk samples treated by ohmic technology the pH value (6.58) and total fatty acids content in milk fat (86.5 mass %) were comparable to those found in milk treated by conventional process, however, ohmically treated samples presented a lower content of lactic acid, 0.13 %. In cloudberry jam samples treated by ohmic technology the results of some of the main parameters tested, such as total sugar content 46.1 mass %, ascorbic acid content 2.83 mass %, and titratable acidity 6.01 mass % (as citric acid) did not show significant differences when compared with samples treated by conventional technology.